Iron Impregnation on Activated Carbon Prepared from Tamarind Wood (Tamarindus Indica L.) as a Potential Catalyst in Biodiesel Production - Astuti, Erna; Suharto, Totok Eka; Setyawan, Martomo; Hanin, Nabila; Mulyono, Sekar Larasati (Universitas Negeri Semarang, 2024)
Renewable energy in the form of biodiesel requires a process called transesterification. This process runs slowly, so a catalyst is needed to reduce the activation energy and speed up the reaction rate. Activated carbon is one of the supports in transesterification catalysts because of its high surface area and is proven to be effective in gas or liquid phase reactions. This work aims to study the potential of active carbon from tamarind wood for making catalysts, the characteristics of the catalyst and the optimal concentration of Fe(NO3)3 in the impregnation step. Activated carbon was impregnated using an Ultrasonic Processor with 80% strength at 60 oC for 60 minutes. The impregnation process was carried out with variations of 2, 4, and 6% Fe(NO3)3 dissolved in 0.09M isopropyl alcohol. Variation of processing time 30, 40, 50, 60, 70, 80 minutes. Furthermore, after the activated carbon is allowed to stand for 24 hours, a calcination process is carried out at 300oC to remove impurities. Obtained materials have been characterized by SEM and XRD. The Fe-impregnation process has been successfully carried out on activated carbon made from Tamarind wood (Tamarindus indica L.). In the Fe precursor solution concentration range of 2 – 6%, the higher the concentration of the Fe precursor solution, the higher the impregnated Fe metal. Fe-impregnated activated carbon has the characteristics of being a material consisting of a mixture of crystalline and amorphous phases with even porous surface morphology. This Fe-impregnated activated carbon is a potential material as a catalyst in the biodiesel production process.